Pengukuran Usability Wastafel Otomatis Berbasis Arduino Menggunakan Metode Use Questionnaire - Suryo Wibowo; Ferida Yuamita (Jurnal Kendali Teknik dan Sains, 2023)
One of the automatic sink products was made by Yogyakarta Technology University students. It is felt that this automatic sink product needs to be tested for its usability or ease of use. The USE questionnaire was used to carry out this test, and five test parameters were used. specifically, learning ability, efficiency, memory, error avoidance, and satisfaction. Based on its use, the purpose of this paper is to find out the user's opinion about the automatic sink product. The distribution of the USE questionnaire consisting of ten questions and five rating points on a Likert Scale was used to conduct this kind of quantitative descriptive research on consumers of automatic sink products. This study obtained usability measurement results for automatic sink products with a value of 84.67% on learnability, 96.22% on efficiency, 82.44% on memoriability, 88% on errors and 76.88% on satisfaction.